2007 Florida Land Value Survey - Rodney L. Clouser; Ronald Muraro; Laila Racevskis; Charles Moss (EDIS)
FE-710, a 6-page fact sheet by Rodney L. Clouser, Ronald Muraro, Laila Racevskis, and Charles Moss, provides estimates of the value of different types of agricultural land for geographic regions of the state, based on a survey conducted in October 2007 for land values in May 2007. Includes references.  Published by the UF Department of Food and Resource Economics, March 2008.